PEREDARAN OBAT ILLEGAL DITINJAU DARI HUKUM PERLINDUNGAN KONSUMEN - Hijawati, Hijawati (Faculty of Law, University of Palembang, 2020)
Every person has the right to live a healthy life, various efforts or methods if someone is sick and wants to deal with his complaint or illness with various medicines in order to recover his condition. In the era of globalization, free trade occurs which results in goods and or services in circulation that do not guarantee the security, safety and health of consumers. The free circulation of illegal drugs is still in demand by some consumers, this is because these drugs are easy to obtain and sell freely at any drug store. Law Number 8 of 1999 concerning Consumer Protection, the Government of Indonesia regulates consumer rights that must be protected. In the Consumer Protection Act, it provides appreciation for consumer rights universally, because consumer protection is part of protecting human rights.